Forensic identification of spilled biodiesel and its blends with petroleum oil based on fingerprinting information. Issue 11 (26th April 2013) - Yang, Zeyu; Hollebone, Bruce P.; Wang, Zhendi; Yang, Chun; Brown, Carl; Landriault, Mike
<x xml:space="preserve">Abstract</x> A case study is presented for the forensic identification of several spilled biodiesels and its blends with petroleum oil using integrated forensic oil fingerprinting techniques. The integrated fingerprinting techniques combined SPE with GC/MS for obtaining individual petroleum hydrocarbons (aliphatic hydrocarbons, polyaromatic hydrocarbons and their alkylated derivatives and biomarkers), and biodiesel hydrocarbons (fatty acid methyl esters, free fatty acids, glycerol, monoacylglycerides, and free sterols). HPLC equipped with evaporative scattering laser detector was also used for identifying the compounds that conventional GC/MS could not finish. The three environmental samples (E1, E2, and E3) and one suspected source sample (S2) were dominant with vegetable oil with high acid values and low concentration of fatty acid methyl ester. The suspected source sample S2 was responsible for the three spilled samples although E1 was slightly contaminated by petroleum oil with light hydrocarbons. The suspected source sample S1 exhibited with the high content of glycerol, low content of glycerides, and high polarity, indicating its difference from the other samples. These samples may be the separated byproducts in producing biodiesel. Canola oil source is the most possible feedstock for the three environmental samples and the suspected source sample S2.